Flattery as a Means to Distort Personal and Social Relationships in Jane Austen’s Novels - Kamboj, Gauri (Journal of Advanced Research in English & Education; Vol 9 No 3 (2024): Journal of Advanced Research in English & Education, 2024)
In literature, sycophants and flatterers serve as critical figures that reflect the complex nature of social hierarchies and interpersonal relationships. Their role often extends beyond mere humour in characterisation; they navigate power dynamics and influence society and its mores, revealing basic truths about human nature and societal conditioning. For example, characters who engage in flattery often use the vulnerabilities of their marks, demonstrating how social and personal relationships can be operated through false praise. This phenomenon is particularly salient in the context of Jane Austen’s novels; flatterers sometimes play pivotal roles in shaping the action and development of relationships. By analysing these interactions, we uncover how Austen overtly criticises the societal structures of her time, reflecting some of the themes present in the 1790s that explored the acceptance of flattery as a form of expected interaction within some relationships in her setting. This paper focuses on how sycophants and flatterers allow us to explore the theme of distortion versus reality in social and personal relationships. The appearance of deference/admiration versus self-serving flattery and falsehood.